Implementasi Aplikasi Jaringan Informasi Bersama Antar Sekolah (JIBAS) Dalam Sistem Akademik Di Pondok Pesantren Daar El Hasanah Jawilan Kabupaten Serang - Munada, Fifi Wardatusshopa; Siti Patimah; Yahdinil Firda Nadhirah; Wasehudin; Rifyal Ahmad Lugowi (Mu'allim, 2025)
This study discusses the implementation of the JIBAS application in the academic information system at the Daar El Hasanah Jawilan Islamic Boarding School. The JIBAS application is used to facilitate the management of academic data digitally, including student data, attendance and others. The purpose of this study is to determine the benefits of the JIBAS application in the academic information system at the Daar El Hasanah Jawilan Islamic Boarding School. The method used in this study is a case study with a qualitative approach. For data collection, namely observation, interviews, and documentation. The results of the study indicate that the JIBAS application improves administrative efficiency, data accuracy, and ease of access to information. Despite facing obstacles such as internet access, limited human resources and user adaptation. The Daar El Hasanah Islamic Boarding School makes improvements such as improving infrastructure, mentoring and training to optimize the use of the academic information system. Thus, the JIBAS application is an effective solution in supporting the management of academic information systems at the Daar El Hasanah Jawilan Islamic Boarding School